Rooting of cuttings of Tibouchina moricandiana. var. vinacea in function of the form of application and concentrations of IBA - Pereira, Mariane de Oliveira; Grabias, Jeniffer; Zuffelatto-Ribas, Katia Christina; Navroski, Marcio Carlos (Revista de Ciências Agroveterinárias, 2015)
Tibouchina moricandiana Baill. var. vinacea Handro is a woody shrub, native to Brazil with ornamental potential. The objective of this study was to evaluate the feasibility of cutting the vegetative propagation of the species according to the application form and different concentrations of indole butyric acid (IBA). Softwood cuttings were treated with 0, 1,000 and 2,000 mg kg-1/mg L-1 of IBA in powder and solution form. After 56 days the treatments were evaluated for rooting, cuttings with callus, survival, mortality, leaf retention, new shoots, number of roots per cutting and root length. The rooting of stem cuttings of T. moricandiana was negatively influenced by the concentrations of IBA or by way of application. The species has a high strike rate (90.8%), demonstrating a species with potential for vegetative propagation through cuttings. The form of application and concentration of IBA influenced other variables. The use of 2,000 mg kg-1 IBA applied by talc demonstrated a decrease in the number of roots and provided the greatest number of and unrooted live cuttings. The length of the three longest roots per cutting was higher with the use of 1,000 mg L-1 or mg kg-1 of IBA. The use of IBA for the rooting of cuttings can be dispensed with, but can be used at a concentration of 1,000 mg-1 or mg kg-1 to increase the length and number of roots.